2021
DOI: 10.1177/00420859211063431
|View full text |Cite
|
Sign up to set email alerts
|

Persistence Despite Structural Barriers: Investigating Work Environments for Black and Latinx Teachers in Urban and Suburban Schools

Abstract: Research suggests that work environments are associated with turnover patterns for teachers of Color. This study investigates variation in work environments using longitudinal administrative data from 20 large urban and suburban K-12 school districts. Results indicate that teachers of Color are more often employed in “hard-to-staff” work environments compared to their White colleagues. Despite this, findings demonstrate high relative levels of teacher experience in schools where teachers of Color, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Importantly, our results indicate that this group of novice teachers was the most ethnoracially underrepresented by their principal, whereby Latinx teachers in our sample were 26 percentage points less likely than novice White teachers to work with a principal who shared their same race/ethnicity. While Latinx teachers are the fastest-growing group of educators in Texas and nationally, prior research suggests that they experience discrimination, stereotyping, and barriers to promotion into leadership positions (Edwards, 2021;Griffin, 2018). In this current study, we found that a Latinx novice teacher was consistently more likely to stay in their current school and less likely to exit the system, compared to a White novice teacher.…”
Section: Increasing Opportunities For Ethnoracial Matchingmentioning
confidence: 39%
See 1 more Smart Citation
“…Importantly, our results indicate that this group of novice teachers was the most ethnoracially underrepresented by their principal, whereby Latinx teachers in our sample were 26 percentage points less likely than novice White teachers to work with a principal who shared their same race/ethnicity. While Latinx teachers are the fastest-growing group of educators in Texas and nationally, prior research suggests that they experience discrimination, stereotyping, and barriers to promotion into leadership positions (Edwards, 2021;Griffin, 2018). In this current study, we found that a Latinx novice teacher was consistently more likely to stay in their current school and less likely to exit the system, compared to a White novice teacher.…”
Section: Increasing Opportunities For Ethnoracial Matchingmentioning
confidence: 39%
“…While Latinx teachers are the fastest-growing group of educators in Texas and nationally, prior research suggests that they experience discrimination, stereotyping, and barriers to promotion into leadership positions (Edwards, 2021; Griffin, 2018). In this current study, we found that a Latinx novice teacher was consistently more likely to stay in their current school and less likely to exit the system, compared to a White novice teacher.…”
Section: Discussionmentioning
confidence: 99%
“…Neoliberal reforms disproportionately impact teachers of color, as they are concentrated in communities where marketized school systems are most prevalent (Castro 2022), "hard-to-staff" schools where pay is less (Edwards 2021), and low-income schools where students are most likely to score lower on standardized tests (Philip and Brown 2020). In 2001, No Child Left Behind (NCLB) began labeling and sanctioning schools with low student performance, as measured by standardized test scores.…”
Section: The Rise and Consequences Of Neoliberal Reform On Teachersmentioning
confidence: 99%
“…In 2015, Every Child Succeeds Act was signed, carrying the baton of neoliberal reform, holding teachers directly accountable for student performance more than in the past (Carver-Thomas and Darling-Hammond 2017). Consequently, a vast body of scholarship shows that teachers of color are overworked, devalued, and feel invisible (Carrillo 2021;Castro 2022;Edwards 2021;Kohli 2021;López 2021;Pizarro and Kohli 2020;Unda 2023).…”
Section: The Rise and Consequences Of Neoliberal Reform On Teachersmentioning
confidence: 99%
“…We used regression modeling to estimate the relationship between key variables. (Edwards, 2021;Griffin, 2018).…”
Section: How This Research Was Donementioning
confidence: 99%